Pengaruh Motivasi, Kompensasi, dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan PT. Arexas Indonesia - Nurmaya, Nurmaya; Yuliani, Tutik (MEDIA RISET EKONOMI [MR.EKO], 2025)
This research aims to determine the partial influence of motivation, compensation and work environment variables on the job satisfaction of PT. Arexas Indonesia employees. This research was carried out at PT Arexas Indonesia Balikpapan, using a sample of 40 contract employees PT. Arexas Indonesia. The data analysis tool used is Smart-PLS. The type of research used is quantitative research. The results of this research indicate that the variables of motivation, compensation and work environment do not influence the job satisfaction of PT. Arexas Indonesia employees.